Bovine colostrum-derived extracellular vesicles protect against non-alcoholic steatohepatitis by modulating gut microbiota and enhancing gut barrier function - Daye Mun; Sangdon Ryu; Daniel Junpyo Lee; Min-Jin Kwak; Hyejin Choi; An Na Kang; Dong-Hyun Lim; Sangnam Oh; Younghoon Kim (Current Research in Food Science)
Non-alcoholic steatohepatitis (NASH), characterized by severe fatty liver-associated inflammation and hepatocellular damage, is a major precursor to cirrhosis and hepatocellular carcinoma. While the exact pathogenesis of NASH remains unclear, gut microbiota dysbiosis has been implicated as a key factor contributing to endotoxin translocation and chronic liver inflammation. Recent studies have highlighted the therapeutic potential of bovine colostrum-derived extracellular vesicles (BCEVs) in modulating gut microbiota and enhancing gut barrier function, but their effects on NASH remain largely unexplored. To investigate the potential protective effects of BCEVs against NASH, 8-wk-old mice were fed a NASH-inducing diet for 3 wks while concurrently receiving oral BCEV administration. BCEV treatment markedly ameliorated hepatic steatosis, fibrosis, and inflammation. Transcriptomic analyses demonstrated a notable reduction in lipid metabolism, bacterial response, and inflammatory pathways in the intestine, as well as reduced expression of inflammation- and fibrosis-related pathways in the liver. Gut microbiota profiling revealed an increased abundance of Akkermansia, accompanied by enhanced cholesterol excretion. Furthermore, BCEV treatment promoted the production of tight junction proteins and mucin in the gut, reinforcing intestinal barrier integrity. These findings suggest that BCEVs promote the proliferation of Akkermansia, which in turn prevents endotoxin translocation to the liver. This reduction in endotoxin leakage alleviates hepatic inflammation and fibrosis. Overall, this study highlights the therapeutic potential of BCEVs as a novel strategy for managing NASH by targeting the gut–liver axis through the modulation of gut microbiota and barrier function.